Optimization of Reducing Sugar Production from Red Algae Biomass through Acid Hydrolysis Using Response Surface Methodology - Ratu Zosa Marchanda; Rhafa Fathanaqi; Ni Ketut Sari; Silvana Dwi Nurherdiana; Renova Panjaitan; Sri Redjeki (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Red algae (Gracilaria sp.) have considerable potential as a renewable biomass resource due to their high polysaccharide content, which can be converted into reducing sugars as a feedstock for biofuel production. This study aimed to evaluate the effects of hydrolysis temperature and time on reducing sugar production and to determine the optimum hydrolysis conditions using Response Surface Methodology (RSM). The research variables consisted of hydrolysis temperatures of 100, 110, 120, 130, and 140°C and hydrolysis times of 20, 30, 40, 50, and 60 min. Prior to hydrolysis, the biomass was dried, milled, and delignified using 2% NaOH at 60°C for 3 h with stirring at 300 rpm. Acid hydrolysis was performed using 0.1 N H?SO? under the specified operating conditions. Reducing sugar content was determined by the Nelson–Somogyi method using UV–Vis spectrophotometry. Data analysis was carried out using Response Surface Methodology (RSM), implemented through Design-Expert software. The results showed that both hydrolysis temperature and time significantly affected reducing sugar production. The highest reducing sugar concentration obtained experimentally was 46.57g/L at 120°C and 40 min. RSM optimization predicted an optimum condition at a hydrolysis temperature of 117.7°C and a hydrolysis time of 42.9 min, resulting in a reducing sugar content of 42.72g/L with a desirability value of 0.992. Model validation demonstrated good agreement between the predicted and experimental values, confirming the reliability of the developed model. These findings indicate that RSM is an effective tool for optimizing reducing sugar production from red algae hydrolysis. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action